PENTINGNYA MENJAGA DAN MENINGKATKAN HUBUNGAN BAIK DENGAN KONSUMEN DALAM MASA KRISIS - Haryono, Tulus (JEJAK: Jurnal Ekonomi dan Kebijakan, 2010)
To maintain and improve customer relationship is the right strategy in the crisis period. This effort can be implemented by marketing relationship strategy. This strategy focus on customer as a partner, who we have to build continuous mutualism relationship. This is a long term relationship which impact on cost efficiency, compared than to get a new customer. This relationship gurantee the companyâs lifetime, so it will be strenghten economic condition.